Variation on Vocal Economy After Different Semioccluded Vocal Tract Exercises in Subjects With Normal Voice and Dysphonia - Calvache, Carlos; Guzman, Marco; Bobadilla, Marcelo; Bortnem, Cori (Journal of voice, 2020)
The present study aimed at observing the possible differential effects of eight semioccluded vocal tract exercises (SOVTE) on vocal economy measured by the Quasi Output Cost Ratio (QOCR). Thirty-six participants were included in this study. They were divided into two groups: an experimental group of subjects diagnosed with mild hyperfunctional dysphonia (n = 17) and a control group of vocally healthy subjects (n = 19). Participants were required to randomly select and produce a series of three SOVTE from a list of eight exercises. The electroglottographic based measure QOCR was used to calculate the vocal economy before and after each voice exercise. Significant differences were found when comparing pre and poststages regardless of the vocal condition (normal voice or dysphonia) or the specific SOVTE used. Moreover, when individually comparing the effect of each SOVTE, only tube in water (10 cm) showed significant differences between pre and postconditions (QOCR values were higher after exercises). In general, semioccluded vocal tract exercises tend to increase vocal economy regardless the vocal condition (normal voice or dysphonia) or the specific SOVTE used. Phonation into a tube submerged deep into water promoted the highest increase in vocal economy. An increased acoustic output, nonproportional increase in vocal folds adduction and an effortless voice production would cause this increase in vocal economy after water resistance therapy.